A Qualitative Study on Local Individual- or Family-Owned Casual Chinese Restaurants Marketing Communication Strategies. Issue 3 (27th May 2021) - Liang, Xuan; Chen, Huan
Abstract: A qualitative study was conducted to examine individual- or family-owned casual Chinese restaurant's marketing communication strategies. Findings revealed that the owners of individual- or family-owned casual Chinese restaurants are highly aware of the importance of advertising for their business. They have adopted at least one marketing strategies to promote their business. Three external factors and one internal factor were found to influence those Chinese restaurant owners' selection of marketing strategies. In addition, the Chinese restaurant owners' personality shapes food and service quality. The findings also suggested that advertising on new media is easier for business owners to measure its effectiveness.